The role of language in international trade: How does language affect the choice of foreign trading partners? - Ribeiro, Sandra (2019)
In an increasingly global and networked economy, companies have a wider market at their disposal but also a number of barriers they have to overcome in order to expand their business internationally. When the decision of trading with another country is made, one of the key issues companies have to deal with is language: language barriers can hinder international trade, while language similarities can boost it due to the weight of communication costs. The economics of language is an interdisciplinary field of study that aims to bring together reflections on the role of language in the economy and conversely on how the economy affects language choices. In this study we focus on the relationship between international trade and language barriers by analysing Portuguese exports of goods and find that language does play an important role in the choice of foreign trading partners although sharing Portuguese as the common language with a group of countries does not imply exporting more to those countries as one might expect. We therefore argue for the increase of multilingual policies in education and more investment in reaping the benefits that Portuguese as an international language might bring to our country.